The ReFi movement in Web3: implications for the Global Commons - Bennett, Kate (Frontiers in Blockchain, 2025)
‘ReFi’ is a rapidly emerging movement in the web3 space that seeks to leverage blockchain technology and decentralized finance (DeFi) protocols to deliver positive real-world impact. While ReFi is short for regenerative finance, regenerative practitioners query the regenerative claims of the movement. This perspective article explains why the regenerative claims of the ReFi movement are under scrutiny and highlights the implications for the Global Commons if the movement does not adhere to regenerative principles. Given that ReFi is a blockchain-enabled movement, the impact of ReFi on the Global Commons is implicitly a blockchain-related concern. This article provides a regenerative practitioner’s perspective on the ReFi movement as a point of reference for blockchain practitioners in the ReFi movement seeking to be a force for good. Long-standing research in ecological economics highlights the negative impacts of over-financialization and commoditization on the natural world. Given that blockchain technology enables more of the world’s natural assets to become commoditized, securitized, and collateralized than ever before, the article asserts that DeFi’s drive to financialize everything could make the Global Commons the next, and final, commodity frontier. It also asserts that the ReFi movement has the potential to reverse this trend if it can genuinely adhere to the regenerative paradigm.